Contributions to the Eocene palaeontology and stratigraphy of Beira Alta, Portugal III - Eocene plant remains from Naia and Sobreda (Beira Alta, Portugal) - Pais, João (2010)
The result of research conducted in trunk fragments from the Coja Arkoses Formation at Naia and Sobreda is reported. It is also reported the palynological study of the lutaceous black level surrounding the Naia trunk. Comparisons with trunks from Nave de Haver are established. Comments on palaeoecology and palaeoclimatology are presented.